Safety Belt Laws and Disparities in Safety Belt Use Among US High-School Drivers - García-España, J. Felipe (American Public Health Association, 2012)
Objectives. We compared reported safety belt use, for both drivers and passengers, among teenagers with learner’s permits, provisional licenses, and unrestricted licenses in states with primary or secondary enforcement of safety belt laws. Methods. Our data source was the 2006 National Young Driver Survey, which included a national representative sample of 3126 high-school drivers. We used multivariate, log-linear regression analyses to assess associations between safety belt laws and belt use. Results. Teenaged drivers were 12% less likely to wear a safety belt as drivers and 15% less likely to wear one as passengers in states with a secondary safety belt law than in states with a primary law. The apparent reduction in belt use among teenagers as they progressed from learner to unrestricted license holder occurred in only secondary enforcement states. Groups reporting particularly low use included African American drivers, rural residents, academically challenged students, and those driving pickup trucks. Conclusions. The results provided further evidence for enactment of primary enforcement provisions in safety belt laws because primary laws are associated with higher safety belt use rates and lower crash-related injuries and mortality.